Prevalence and Predictors of Arrhythmia in Patients with Obstructive Sleep Apnea - Almeneessier, Aljohara Saud; Alasousi, Nader; Sharif, Munir M; Pandi-Perumal, Seithikurippu R; Hersi, Ahmad Salah; BaHammam, Ahmed Salem (Sleep Science, 2017)
Objectives To assess the prevalence and types of arrhythmias in Saudi OSA patients and to identify predictors of arrhythmia in this group of patients.METHODS This case-control study included all patients who underwent level I attended overnight polysomnography between 2009 and 2012. Electrocardiographic data collected during sleep studies of patients with and without OSA were manually reviewed.Results The study comprised 498 patients (394 OSA patients and 104 non-OSA patients (controls). The prevalence of arrhythmia in OSA patients was higher than that in the controls (26.9% vs. 11.5%; p=0.001). Comparing OSA patients and controls showed: premature atrial contraction (10.2%vs.2.9%;p=0.019), premature ventricular contraction (PVC) (19.3%vs.9.6%;p=0.02), non-isolated PVC (bi/tri/qua) 10.8%vs.2.3%;p=0.04) and atrial fibrillation (1.6%vs.0%;p=0.001). Multiple logistic regression analysis revealed that, patients with OSA had twice the odds of having any cardiac arrhythmia (OR 1.91; CI 95% 1.27-3.11; p <0.05).Conclusions Patients with OSA had a higher prevalence of arrhythmia compared to controls, and OSA is a predictor of arrhythmia during sleep.
Keywords: Atrial fibrillation; Sleep Apnea, Obstructive, Arrhythmias, Cardiac